Institutionalized zakāh in addressing well-being problems in non-Muslim Majority Sri Lanka - Salithamby, Abdul Rauff; A. Hatta, Zulkarnain; Fahrudin, Adi (Journal of King Abdulaziz University: Islamic Economics, 2022)
Institutionalized zakāh has long been a decisive tool that provides various types of support to addressing a variety of well-being problems of the Muslim community in Sri Lanka, a country where such a community is a minority. Being significantly successful to empowering the underprivileged of the community, the zakāh has also faced challenges that negatively impacted its effective functioning. This study aimed to investigate institutionalized zakāh’s multiple support, identifying its challenges and suggesting some recommendations to make its’ role more effective. This is an exploratory study used qualitative data collected through interviews with five zakāh institutions in the Eastern part of the country. The findings showed that: zakāh provided the target community with access to basic needs, economic opportunities and assistance for higher education. However, the shortage of professional and properly trained human resources, misuse of support, lack of beneficiary monitoring mechanism, and lack of community awareness on zakāh were all identified as prime challenges that have to be addressed to attain the utmost benefits from the embedded potential of zakāh.